Quality of essential newborn care and neonatal resuscitation at health facilities in Afghanistan: a cross-sectional assessment. Issue 8 (August 2019) - Atiqzai, Faridullah; Manalai, Partamin; Amin, Sher Shah; Edmond, Karen M; Naziri, Malalai; Soroush, Mohammad Samim; Sultana, Sharmina; Yousufi, Khaksar; van den Akker, Thomas; Stekelenburg, Jelle; Tappis, Hannah
Abstract : Objective: To assess readiness and quality of essential newborn care and neonatal resuscitation practices in public health facilities in Afghanistan. Design: Cross-sectional assessment. Setting: 226 public health facilities in Afghanistan, including 77 public health facilities with at least five births per day (high-volume facilities) and 149 of 1736 public health facilities with fewer than five births per day (low-volume facilities). Participants: Managers of 226 public health facilities, 734 skilled birth attendants (SBAs) working at these facilities, and 643 women and their newborns observed during childbirth at 77 high-volume health facilities. Outcome measures: Availability of knowledgeable SBAs, availability of supplies and compliance with global guidelines for essential newborn care and neonatal resuscitation practices. Results: At high-volume facilities, 569/636 (87.9%) of babies were dried immediately after birth, 313/636 (49.2%) were placed in skin-to-skin contact with their mother and 581/636 (89.7%) had their umbilical cord cut with a sterile blade or scissors. A total of 87 newborn resuscitation attempts were observed. Twenty-four of the 87 (27.5%) began to breath or cry after simply clearing the airway or on stimulation. In the remaining 63 (72.5%) cases, a healthcare worker began resuscitation with a bag and mask; however, only 54 (62%) used a correct size of mask and three babies died as their resuscitation with bag and mask was unsuccessful. Conclusions: The study indicates room for improvement of the quality of neonatal resuscitation practices at public health facilities in Afghanistan, requiring only strengthening of the current best practices in newborn care. Certain basic and effective aspects of essential newborn care that can be improved on with little additional resources were also missing, such as skin-to-skin contact of the babies with their mother. Improvement of compliance with the standard newborn care practices must be ensured to reduce preventable newborn mortality and morbidity in Afghanistan.